A facile solution-phase synthetic approach for constructing phenol-based porous organic cages and covalent organic frameworks. Issue 8 (1st April 2020) - Zhang, Lei; Liang, Rongran; Hang, Cheng; Wang, Haiying; Sun, Lin; Xu, Lei; Liu, Dairong; Zhang, Zhenyi; Zhang, Xingmin; Chang, Feifan; Zhao, Shengyu; Huang, Wei
Abstract : A general solution-phase synthetic strategy is developed to construct both porous organic cages (POCs) and covalent organic frameworks (COFs) by simply stirring and heating organic solvent/water solutions of aldehydes and amines in the presence of MOH (M = Na, K, and Cs). Abstract : Porous crystalline materials, such as porous organic cages (POCs) and covalent organic frameworks (COFs), are important for a wide range of applications such as gas storage/separation, sensing and catalysis. A conventional synthetic approach for imine-based POCs and COFs usually involves the use of organic solvents/acid catalysts (such as AcOH or TFA). However, synthesizing and growing POC crystals and COF crystallites with enhanced crystallinity is not an easy-to-perform process, in which many reaction parameters need to be screened. To overcome these problems, we have proposed herein a facile and green synthetic strategy by adopting H2 O/organic solvents/MOH (M = Na, K, and Cs) as reaction media to produce a series of phenol-based POCs and COFs. X-ray crystallography and molecular simulations have been used to confirm their structures in addition to NMR, mass and FT-IR spectra, and gas sorption experiments reveal their porosity and sorption properties. This new approach provides not only an efficient and alternative route to synthesize highly crystalline POCs and even COFs, but also insight into the crystallization process of these two kinds of porous materials, especially in the hydrous media.